How to manage QT prolongation in COVID-19 patients - sidhi laksono purwowiyoto; Dony Yugo Hermanto; Muhammad Iqbal (The Indonesian Heart Association, 2020)
Indonesia has declared a COVID-19 outbreaks because of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in March 2020. COVID-19 has significantly increased morbidity and mortality worldwide. Some studies have shown good clinical outcomes with the use of combination of chloroquine or hydroxychloroquine and azithromycin. That drugs can prolong the QT interval and increase the risk of Torsade de Pointes (TdP). The risk is increasing in several conditions such as in critical patients, metabolic disorders, sepsis, multiorgan dysfunction and with drug-drug interactions. Cardiologists need to know how to manage this condition to reduce the risk of TdP.